(untitled) (Asian Journal of Current Engineering and Maths, 2013)
This paper is concerned with the study of certain basic type of semigroupsknown as variants of semigroups.The motivation to prove the theorems in thispaper is due to the results of J.M.HOWIE[ 5 ], G.Shobhalatha and A .R ajeswaribhat [2]